Unpacking Relational Dignity: In Pursuit of an Ethic of Care for Outdoor Therapies - Harper, Nevin J.; Fernee, Carina Ribe (Frontiers in Psychology, 2022)
Dignity is a universal principle that requires us to treat every person as having worth beyond who a particular person is or what they do. Dignity is a complex and sometimes contested idea, that at times can be compromised in health care and allegedly also within the practice of outdoor therapy. Outdoor therapies comprise a range of therapeutic approaches including nature-based therapy, adventure therapy, animal-assisted therapy, forest therapy, wilderness therapy, surf therapy and more. Within the literature of outdoor therapies there has been limited research on ethics related to common understandings of care concepts such as relational dignity and human rights. The aim of this paper is therefore to unravel briefly whether dignity in general, and relational qualities of dignified care more particularly, might be a useful concept to apply in order to support an ethical practice in outdoor therapies.